AB0790 Which Score to Use for Radiographic Damage Assessment of the Spine in (Early) Axial Spondyloarthritis? Two-Year Data From the Desir Cohort. (9th June 2015) - Ramiro, S.; Claudepierre, P.; van den Berg, R.; Navarro-Compán, V.; Feydy, A.; D'Agostino, M.A.; Loeuille, D.; Dougados, M.; Reijnierse, M.; van der Heijde, D.
Abstract : Background: Several scores have been developed to assess radiographic damage in ankylosing spondylitis (AS). However, we do not know how they perform in early phases of the disease. Objectives: To compare the performance of different radiographic scores of the spine in patients with early axial spondyloarthritis (axSpA). Methods: Yearly radiographs from a 2-year follow-up of the DESIR cohort from patients fulfilling the ASAS axSpA criteria have been used. Spinal (cervical, thoracic and lumbar) and sacro-iliac (SI) radiographs were scored independently by two readers for the presence of the different damage aspects enabling the calculation of different scores: mSASSS (0-72), SASSS (0-72), RASSS (0-84) and BASRI-spine (0-12), using the averaged scores between readers per vertebral corner (VC)/SI joints. Additionally, a variation of the BASRI-spine was computed adding an overall score for the thoracic spine (0-16). Following the OMERACT proposal, scores were compared with regard to truth, discrimination (sensitivity to change and reliability) and feasibility. Status (at baseline or first x-ray available) and 2-year progression scores were calculated for each of the methods as well as the proportion of patients with any change (change>0). Results: In total, 486 patients (mean age 33.0 (SD 8.6) years, 50% males) had at least one radiograph available. At baseline, scores ranged from 0 and 21.6 for the mSASSS (30% of the maximum of the scale), 20.6 for RASSS (25% of maximum), 6 for SASSS (8% of maximum), 8.5 for BASRI-spine (71% of maximum) and 10.25 for BASRI-spine with thoracic spine (64% of maximum). Status scores and 2-year progression scores available are shown in the table. The proportion of patients with any 2-year change was the following: 9.9% for mSASSS, 10.7% for RASSS, 6.9% for SASSS, 19.2% for BASRI-spine and 22.0% for BASRI-spine with thoracic spine. Absolute change scores (table ) showed that the mSASSS and RASSS captured most change. 2-year RASSS progression occurred in a balanced way across segments (cervical, thoracic and lumbar), when taking the number of VCs included per segment. All scores had acceptable reliability. In what concerns feasibility, all scores seemed to be feasible, but the BASRI-spine (+/- thoracic spine) was more frequently missing (up to 15% of the cases), as it requires also the availability of SI joints. Conclusions: The existing scoring methods to assess radiographic damage performed well in early phases of axSpA. The mSASSS and RASSS captured most change, but there was no gain in additionally scoring the thoracic spine for the RASSS. The mSASSS remains the most sensitive and most adequate scoring method in axSpA, including early phases of the disease. Disclosure of Interest: None declared